Valencià «versus» castellà als segles XVIII i XIX. El cas de Vicent Salvà - Casanova, Emili (Caplletra. Revista Internacional de Filologia, 2015)
The aim of this article is to look into the field of the linguistic altitudes of enlightened people, with some notes about the importance of the Castilian language in Valencia in the xviii and xix centuries. It considers particularly teaching methods of this language, expositions of the original lexicography of the age and, in particular, the contribution of the Valencian grammarian Vicent Salvà.